Study of the influence of using circuit training for the education and development of the coordination skills of U16 handball players - Cristea-Mic, N.; Costea, L. M. (Annals of "Dunarea de Jos" University of Galati: Physical Education and Sport Management, 2020)
This study seeks to use complex means (circuit training), which will lead to technical improvements in U16 male handball, along with the development of conditional and coordinating skills. The sample of the study consisted of two groups of subjects (experimental and control) consisting of 21 and 17 athletes respectively. The selected subjects were handball players from Bucharest Municipal Sports Club - the experimental group, and athletes of the handball team from School Sports Club No. 2 Bucharest - the control group. The results obtained have shown that the specific means and materials used by us during the application stages of the training of the male handball players, led to the optimization of the technical training by enriching the motor repertoire, the development of conditional and coordinating skills, the consolidation and improvement general and specific motor skills.